Increased Red Cell Distribution Width Is Associated With Disease Severity in Hospitalized Adults With SARS-CoV-2 Infection: An Observational Multicentric Study - Karampitsakos, Theodoros; Akinosoglou, Karolina; Papaioannou, Ourania; Panou, Vassiliki; Koromilias, Athanasios; Bakakos, Petros; Loukides, Stelios; Bouros, Demosthenes; Gogos, Charalampos; Tzouvelekis, Argyrios (Frontiers in Medicine, 2020)
Background: There is an amenable need for clinically applicable biomarkers in patients with SARS-CoV-2 infection. Red Cell Distribution Width (RDW) has been recently suggested as a prognostic biomarker for COVID-19. Methods: This was an observational study enrolling patients between February 26 and May 15 2020. We aimed to validate the association of the previously published RDW threshold of 14.5% with markers of disease progression and mortality. Results: A total number of 193 hospitalized patients with COVID-19 were enrolled and analyzed. Median age was 61 years (95% CI: 58 to 64). Patients with baseline RDW ≥14.5% (n= 41, 19.2%) presented with more progressive disease compared to patients with baseline RDW<14.5% (n=156, 80.8%) as indicated by significant differences in maximum FiO2% during hospitalization (median: 100, 95% CI: 45.2 to 100, vs. 35, 95% CI: 31 to 40, p=0.0001, respectively). Values of RDW ≥14.5% were also strongly associated with increased risk of mortality (HR: 4.1, 95% CI: 0.88 to 19.23), (p=0.02). Conclusion: Our study provides evidence to support reproducibility and validity of a specified cut-off threshold of RDW as biomarker of disease severity and mortality in patients with COVID-19.